Innovation sociale | social innovation - - Travaux publics et Services gouvernementaux Canada Gouvernement du Canada (2015)
The creation, development, adoption and integration of new and renewed concepts and practices that put people and the planet first. Tiré de Internet. [http://socialinnovation.ca]. Centre for Social Innovation. "What the heck is social innovation?" (20140813)
Keywords: Bases de données terminologiques; Canada; Libre accès